A Simplified Electroencephalography Montage and Interpretation for Evaluation of Comatose Patients in the ICU. (3rd November 2022) - Abid, Sonia; Papin, Gregory; Vellieux, Geoffroy; de Montmollin, Etienne; Wicky, Paul Henri; Patrier, Juliette; Jaquet, Pierre; Bouadma, Lila; Rouvel-Tallec, Anny; Timsit, Jean-François; Sonneville, Romain
Abstract : OBJECTIVES: Electroencephalography (EEG) is one of the main tools for diagnosis and prognostication of encephalopathy. Our two objectives were to assess: 1) the reliability of intensivists' interpretations (one trained intensivist and nonexpert intensivists) on specific EEG patterns and 2) the feasibility of performing simplified EEG by a trained intensivist in ICU. DESIGN: Prospective, single-center study. SETTING: One French tertiary-care center. PATIENTS: Thirty-six consecutive ICU patients with encephalopathy. INTERVENTION: A trained intensivist (1-year specific electrophysiologic course) recorded and interpreted EEGs using a 10 monopod montage at bedside. Then, 22 nonexpert intensivists underwent a 1-hour educational session on interpretation of EEG background (activity, continuity, and reactivity) and common patterns seen in ICU. Trained and nonexpert intensivists' interpretation of EEG recordings was evaluated and compared with an expert neurophysiologist's interpretation (gold standard). The agreement between the two interpretations was evaluated. Second, the duration of the entire EEG procedure (specifically EEG installation) at bedside was recorded. MEASUREMENTS AND MAIN RESULTS: Agreements and reliability between the trained intensivist and the neurophysiologist were acceptable for minimal (agreement, 94%; Pearson coefficient, 0.60) and maximal (89%, 0.89) background frequency, burst suppression (agreement, 100%; Kappa coefficient, 1), background continuity (83%, 0.59), and reactivity to auditory stimulus (78%, 0.44). Agreements between the 22 nonexpert intensivists and the neurophysiologist were heterogeneous. As a result, 87% of the 22 nonexpert intensivists obtained an acceptable reliability for the minimum background frequency, 95% for the maximum background frequency, and 73% and 95% for burst suppression and isoelectric background identification, respectively. The median duration of the entire EEG procedure was 47 minutes (43–53 min), including 22 minutes (20–28 min) of EEG installation. CONCLUSIONS: Intensivists can rapidly learn background activity and identify burst-suppression and isoelectric background. However, more educational sessions are required for interpretation of other EEG patterns frequently observed in the ICU setting.